MicroRNA-145 Increases the Apoptosis of Activated Hepatic Stellate Cells Induced by TRAIL through NF-κB Signaling Pathway - Junfa Yang; Junfa Yang; Junfa Yang; Qingxue Liu; Qingxue Liu; Qingxue Liu; Shiyang Cao; Shiyang Cao; Shiyang Cao; Tao Xu; Tao Xu; Tao Xu; et al. (Frontiers Media S.A., 2018)
During the liver fibrosis recovery stage tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) can effectively induce apoptosis of activated hepatic stellate cells (HSCs). Normal hepatic stellate cells are resistant to TRAIL cytotoxicity. Therefore, enhancing the sensitivity of TRAIL-induced apoptosis of HSCs may be useful to treat hepatic fibrogenesis. Here, we demonstrated that miR-145 and TRAIL were down-regulated in both liver fibrosis tissue samples and transforming growth factor-β1 induced HSCs, concomitant with increased the expression of ZEB2. In addition, we found that mimics-mediated over-expression of miR-145 led to resistance to the ZEB2 expression and up-regulation of the TRAIL-induced apoptosis after treatment of LX-2 cells with TRAIL. Furthermore, ZEB2-siRNA transfected LX-2 cells showed the increased sensitivity to TRAIL-induced apoptosis. Whereas, opposite results were obtained in miR-145-inhibitor group or ZEB2 plasmid group. Moreover, miR-145 regulated ZEB2 gene expression by specifically interacting with the 3'-UTR of ZEB2 mRNA to inhibit the expression of ZEB2. Further studies showed that the over-expression of ZEB2 could inhibit TRAIL-induced apoptosis via inhibiting nuclear factor-κB (NF-κB) signaling pathway in LX-2 cells. Collectively, our data suggest that up-regulation of miR-145 can down-regulate ZEB2 expression, consequently promoting TRAIL-induced apoptosis in LX-2 cells through NF-κB signaling pathway, which facilitates the resolution of liver fibrosis.